Drilling Effectively in The Target Zone Using a Smart Alert System to Reduce Non-Productive Time in Geosteering Operations - Yustian Rahanjani; Budhi Nugraha (Testing Center for Oil and Gas LEMIGAS, 2025)
This paper discusses the benefits of using a smart alert system for the detection of geological boundaries, and how this system enhances decision making during geosteering operations. Monitoring multiple wells in a high operation environment is a big challenge for geosteering operations. Using Managed By Exception (MBE), an integrated smart system that produces an alert when the well deviates from the target zone while drilling is a solution which can greatly improve operations efficiency. Real-time drilling data is processed through the integrated alert system by a set of algorithms that can recognize when the drill-bit goes out of the reservoir. This is based on Logging While Drilling (LWD) characteristics. The smart system can then recommend if an adjustment in inclination is required to keep the best contact with the reservoir. This creates a seamless geosteering workflow. Geologists and petrophysicists can now leverage a comprehensive understanding of real-time data infrastructure, log formats, and data processing. This fosters effective communication about reservoir condition We believe MBE setup significantly improves geosteering efficiency and encourages others to utilize the power of real-time data analysis.